The Introduction of a ‘Therapy Dog’/‘Engagement Dog’ to Support the Work of the Youth Advisor - Lisa Howarth (JANZSSA)
The Youth Advisor (Lisa Howarth) currently works to support young people up to 25 years of age to have the best possible learning experience whilst studying at CIT. This is achieved by developing connectivity between the young people and existing services offered at CIT (including counsellors, CITSA, study support, etc) and outside organisations; working with teachers to develop curriculum/classroom management practices that reflect and support the needs of younger learners; initiating and developing collaborative relationships between CIT and other organisations that support young people; and, most importantly, spending time in the (CIT) social spaces of the young people . A large portion of the Youth Advisor’s time is spent ‘hanging out’ in the social spaces with young people to build relationships and be available to discuss issues that may affect their ability to study effectively. The majority of the Youth Advisor’s time and work is with ‘disconnected’ and ‘disengaged’ young people.